Sikap Merek dan Romansa Merek sebagai Faktor Penentu Kesetiaan Merek di Ducati Owners Club Yogyakarta - , CIPTA NUR SATRIA ADI, Bayu Sutikno, M.S.M., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This âBrand Attitude and Brand Romance as Determinants of Brand Loyalty in The Ducati Owners Club Yogyakartaâ research aims to examine the influence of brand attitude towards brand romance, brand attitude towards brand loyalty, and brand romance towards brand loyalty. This research took place in Yogyakarta and uses 43 owners of Ducati motorcycles that belong to brand community Ducati Owners Club (DOC) Yogyakarta as respondents. The findings generated in this study is brand attitude does not have a positive influence on brand romance. Furthermore, brand attitude has a positive influence on brand loyalty, and brand romance has a positive influence on brand loyalty.